Public Transportation Development in Smart Forest City Based on Cloud Computing - Li Ya (Forest Chemicals Review)
The intelligent level of public transportation in smart forest city is an important symbol of urban development and industrial manufacturing development. Urban road network in smart forest city is a kind of complex network. Complex network theory is an important branch of complex systematic science. At first, complex networks are used to describe the interrelated theories in natural and Social Sciences and engineering technology. Later, they have been widely used in other fields, and become one of the hot topics in many disciplines. This paper uses the theory of complex network knowledge, combined with the intelligent algorithm developed in modern times, to generate and optimize the urban public transport network. The optimization of urban public transport network is mainly for the convenience of residents’ travel and urban development. Starting from the topological structure, this paper analyzes the mutual attraction relationship of public transport traffic volume between nodes, and combines with genetic algorithm to determine the optimal route selection. Finally, we get the urban public transport network to meet the urban development and residents’ travel needs.